Severe Symptomatic Hyponatremia Secondary to Escitalopram-Induced SIADH: A Case Report with Literature Review - Rishi Raj; Aasems Jacob; Ajay Venkatanarayan; Mohankumar Doraiswamy; Manjula Ashok (Case Reports in Nephrology)
Hyponatremia is a well-known medication related side effect of selective serotonin reuptake inhibitors; despite its association with escitalopram, the newest SSRI is very rare. We did a review of literature and came across only 14 reported case of this rare association of SIADH with escitalopram. We hereby report a case of a 93-year-old female who presented with generalized tonic-clonic seizure and was diagnosed with severe hyponatremia due to escitalopram-induced syndrome of inappropriate antidiuretic hormone secretion (SIADH). With this article, we want to emphasize clinicians about this rare side effect of escitalopram use and look for the risk factors leading to SIADH.